PROSPECTS FOR USING THE STEAM APPROACH1 IN THE EDUCATIONAL PROCESS - Pazilova Shokxida Abdulbasitovna (Bright Mind Publishing, 2025)
This article examines the compatibility of the Steam approach with the ability for self-learning and teamwork, and the benefits of an effective interactive learning approach. The article describes how the STEAM approach differs from the traditional type of learning and how students' thinking develops.
Keywords: STEM integration, STEAM, education, natural sciences, technology, engineering, mathematical sciences.